2021
DOI: 10.1039/d1qo01013a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-chromanone-fused [3.2.0] bicycles through a phosphine-mediated tandem [3 + 2] cyclization/intramolecular Wittig reaction

Abstract: A phosphine-mediated tandem [3+2] cyclization/intramolecular Wittig reaction of 3-aroylcoumarin with alkynone is described. The high efficiency of tandem process allows the synthesis of 2-chromanone-fused bicyclo[3.2.0]heptenones in moderate to high yields...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…[80] The allylic phosphorus ylide 200 generated from 2 f and PPh 3 undergoes γ-addition to the ketone 117 e for the In 2021, Han and coworkers reported the phosphine mediated tandem [3 + 2] annulation/intramolecular Wittig reaction from 3-trifluoroacetyl-chromenones 205 and alkynones 176 to afford trifluoromethylated 2chromanone fused bicyclo[3.2.0]heptenones 206 in low to high yields (up to 87%, Scheme 32). [81] Voituriez et al reported a conceptually distinct phosphine (via P III /P V =O redox cycle) catalyzed asymmetric tandem Michael addition/Wittig of 4,4,4-trifluorobutane-1,3-diones 211 or CF 3 -dihydro-1H-indenones 213 with dialkyl acetylenedicarboxylates 210 to afford fluorinated cyclobutenes 212 or spiro [3.4]octanones 214, respectively, in good to excellent yields (up to 99%) and enantioselectivities (up to 95% ee). In this process, the chiral trivalent phosphines (in situ reduced from the phosphine oxides P13 and P14 with phenyl silane) were used as the nucleophilic catalysts (Scheme 33).…”
Section: Annulation Reactionsmentioning
confidence: 99%
“…[80] The allylic phosphorus ylide 200 generated from 2 f and PPh 3 undergoes γ-addition to the ketone 117 e for the In 2021, Han and coworkers reported the phosphine mediated tandem [3 + 2] annulation/intramolecular Wittig reaction from 3-trifluoroacetyl-chromenones 205 and alkynones 176 to afford trifluoromethylated 2chromanone fused bicyclo[3.2.0]heptenones 206 in low to high yields (up to 87%, Scheme 32). [81] Voituriez et al reported a conceptually distinct phosphine (via P III /P V =O redox cycle) catalyzed asymmetric tandem Michael addition/Wittig of 4,4,4-trifluorobutane-1,3-diones 211 or CF 3 -dihydro-1H-indenones 213 with dialkyl acetylenedicarboxylates 210 to afford fluorinated cyclobutenes 212 or spiro [3.4]octanones 214, respectively, in good to excellent yields (up to 99%) and enantioselectivities (up to 95% ee). In this process, the chiral trivalent phosphines (in situ reduced from the phosphine oxides P13 and P14 with phenyl silane) were used as the nucleophilic catalysts (Scheme 33).…”
Section: Annulation Reactionsmentioning
confidence: 99%
“…tion/intramolecular Wittig cyclization from 3-aroylcoumarin and alkynone (Scheme 1b). 11 Very recently, coumarinfused cyclopentanones were selectively afforded in moderate to good yields with excellent diastereoselectivities under phosphine catalysis of 3-benzoyl coumarin with alkynone (Scheme 1c). 12 As part of our ongoing research pursuit, herein, we disclose a direct and efficient access to coumarin-based CF 3 -containing furanones under mild reaction conditions (Scheme 1d).…”
Section: Letter Synlettmentioning
confidence: 99%
“…The heterocyclic product of CF 3 -containing furanone 3a could be isolated in 66% yield by using trifluoroethanol as solvent with 100 mol% of PPhEt 2 (entry 10). The subsequent influence of phosphines on the reaction was investigated (entries [10][11][12][13][14][15].…”
Section: Letter Synlettmentioning
confidence: 99%
“…To further improve the yield of 3a, different solvents, PPh 3 loadings, and various temperatures were surveyed (Table 1, entries [7][8][9][10][11][12][13][14][15]. The screening results revealed that solvent (Table 1, entries 7-9) and temperature (Table 1, entries 12-15) significantly affected the reaction performance.…”
Section: Letter Synlettmentioning
confidence: 99%
“…12 In 2021, we demonstrated a phosphine-mediated tandem [3+2] cyclization/intramolecular Wittig reaction of 3-aroylcoumarin with alkynone. 13 On the basis of our continuous interest in exploring new reactions of ynones, herein we report a phosphine-promoted [3+2] cascade annulation reaction of functionalized 3benzoyl coumarin with alkynone under a mild reaction conditions. By variation of the nucleophilicity of phosphines, two classes of coumarin-fused cyclopentanones were selectively afforded in moderate to good yields with excellent diastereoselectivities.…”
mentioning
confidence: 99%